2021
DOI: 10.3390/ijerph18031070
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Appeal of Environmental Values Influence Sustainable Entrepreneurial Intention?

Abstract: Global challenges posed by climate change and environmental deterioration are increasingly driving entrepreneurship with sustainable entrepreneurial intention as a key driver in predicting entrepreneurial activities. Together with experience, the environmental values of an entrepreneur are vital for sustainable entrepreneurial intention. However, the extent to which experience is a key factor to start up a sustainable enterprise is still rather unclear. To study the role of experience, we derive from the theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 52 publications
2
26
0
2
Order By: Relevance
“…Personal values are the principles that guide human behavior and are also essential predictors for entrepreneurial intention [68,69]. Therefore, differences in values produce various entrepreneurial intentions and activities [70][71][72].…”
Section: Personal Variables Of Entrepreneurshipmentioning
confidence: 99%
“…Personal values are the principles that guide human behavior and are also essential predictors for entrepreneurial intention [68,69]. Therefore, differences in values produce various entrepreneurial intentions and activities [70][71][72].…”
Section: Personal Variables Of Entrepreneurshipmentioning
confidence: 99%
“…The emergence of interest in a person's behavior is influenced by the emergence of the initial attitude of the person. Several studies have shown that attitude toward behavior has a positive and significant effect on green entrepreneurial intentions (Vuorio et al, 2018;Thelken & de Jong, 2020;Nordin, 2020;Yasir et al, 2021;Peng et al, 2021). While the research by Sargani et al (2020), shows that attitude towards behavior does not affect green entrepreneurial intentions.…”
Section: Introductionmentioning
confidence: 98%
“…According to the theory of planned behavior, subjective norm involves the social pressure felt by a person from the majority of people who are important to him, which the individual considers whether to perform the behavior. Several studies have shown that Subjective Norm has a positive and significant effect on Green Entrepreneurial Intentions (Sargani et al, 2020;Londono et al, 2020;Yasir et al, 2021;Peng et al, 2021). Meanwhile, other research shows that Subjective Norm does not affect Green Entrepreneurial Intentions (Ranasinghe & Ajward, 2019;Nordin, 2020;Thelken & de Jong, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that the creation of companies involves the planning of behavior on the part of the individual, the literature has shown that the behavioral intention models; considering aspects about culture, social, educational, and family environment; are robust in this field of research on entrepreneurial intention [9]. In particular, the Theory of Planned Behavior (TPB) [10,11], had been widely used in various areas to predict different types of behavioral intentions [12][13][14][15][16]. As many authors claim, TPB constitutes the most widely used model in the study of EI in different countries [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%